Structure and kinematics of early-type galaxies from integral field spectroscopy - Cappellari, M (Annual Reviews, 2016)
Observations of galaxy isophotes, long-slit kinematics, and high-resolution photometry suggested a possible dichotomy between two distinct classes of elliptical galaxies. But these methods are expensive for large galaxy samples. Instead, integral field spectroscopy can efficiently recognize the shape, dynamics, and stellar population of complete samples of early-type galaxies (ETGs). These studies showed that the two main classes, the fast and slow rotators, can be separated using stellar kinematics. I show that there is a dichotomy in the dynamics of the two classes. The slow rotators are weakly triaxial and dominate above Mcrit ≈ 2 1011 M . Below Mcrit, the structure of fast rotators parallels that of spiral galaxies. There is a smooth sequence along which the age, the metal content, the enhancement in α-elements, and the weight of the stellar initial mass function all increase with the central mass density slope, or bulge mass fraction, while the molecular gas fraction correspondingly decreases. The properties of ETGs on galaxy scaling relations, in particular the (M*, Re) diagram, and their dependence on environment, indicate two main independent channels for galaxy evolution. Fast-rotator ETGs start as star-forming disks and evolve through a channel dominated by gas accretion, bulge growth, and quenching, whereas slow rotators assemble near the centers of massive halos via intense star formation at high redshift and remain as such for the rest of their evolution via a channel dominated by gas poor mergers. This is consistent with independent studies of the galaxies redshift evolution.